Pengendalian Banjir Pada Daerah Aliran Sungai Pesanggrahan Menggunakan Pemodelan HEC-RAS - Habibi, Naufal Ilham; Darmawan, Yahya (Jagratara: Journal of Disaster Research, 2024)
Flooding is one of the most common threats in Indonesia. The disaster generally occurs during the rainy season due to high rainfall. The inability of the watershed to accommodate the rain causes the water to overflow and inundate the surrounding area. The Pesanggrahan watershed is one example with a dense population. This hampers activities, economic losses, and health problems. Efforts are needed to prevent flood disasters. One of them is flood modelling using HEC-RAS. The purpose of the research focuses on the application of the HEC-RAS model in the Pesanggrahan watershed to determine the boundaries of water levels and overflows that have the potential to flood. The benefit of the research is to control flooding. The research was conducted in the Pesanggrahan watershed with coordinates of 6o 10' 20" - 6o 33' 50" N-S and 106o 44' 15" - 106o 48' 05" EAST. Data used in the form of rainfall comes from the Ciliwung-Cisadane River Basin and DEM and shp from USGS, and Geospatial Information Agency. Data were analysed using quantitative and qualitative methods of Log Pearson Type III distribution and Chi-Square and Smirnov-Kolmogorof tests, as well as the Mononobe method for rainfall plans. The results of the study are Q2th = 217.03 m3/s, Q5th = 305.34 m3, Q10th = 364.69 m3/s, Q25th = 440.49 m3/s, Q50th = 487.52 m3/s. The highest River Station 53135 is in the upper reaches of the river with an average height of 4 - 6 metres and the lowest 35 is in the lower reaches of the river with an average height of 3 - 4 metres. It also appears that there are many overflows in the DKI Jakarta area. Therefore, there is a need for flood management.